Study on safety behavior planning theory and control strategies for coal chemical workers. (August 2020) - Min, Yao; Yexiang, Fang; Weilin, Tang; Jiajie, Zhou
Highlights: We extend the theory of planned behavior. The behavior theory of safety planning is constructed and tested by ISM-SEM. The safety planning behavior model of management level is constructed. Abstract: As a new industry, coal chemical industry is a high-risk industry with large investment scale, long process and complex technology. Its personnel come from coal mine, petroleum and petrochemical industry, and their quality and safety perception are different. Their behavior pattern has the characteristics of both coal mine and chemical industry, resulting in huge potential risk of personnel behavior. It is very important to study the safety behavior model of front-line workers under the management system of coal chemical industry. Based on the theory of planned behavior and the theory of prospect, this paper puts forward a model of safety behavior planning. In order to verify the model, the coal chemical front-line employees are taken as the research object. Firstly, through the comprehensive application of psychology, behavioral theory and previous research results of safety human factors, a more comprehensive index of safety factors on the spot is constructed, in which safety plan behavior elements are mixed. This paper explores the mechanism among many factors, collects index data through safety perception questionnaire, and uses DEMATEL-SIM system analysis method to analyze the system structure model of the influencing factors of field safety. The structure model supports the safety behavior planning model. Then the structural equation model is constructed to validate the safety behavior planning model, and the empirical research is carried out. The results show that there is a safety behavior planning model under the coal chemical management system, and the corresponding control countermeasures are given.